A278 TB OR NOT TB OF THE PANCREAS. (26th February 2020) - Chis, R; Tartaro, P
Abstract: Background: Pancreatic TB is a rare clinical presentation which has proved difficult to diagnose. Its symptomatology and imaging characteristics mimic neoplastic findings. Aims: We present the case of a previously healthy 58-year-old man, from an endemic area who presented with epigastric pain caused by pancreatic TB. Methods: Case report and review of literature Results: A previously well 58-year-old male presented to the emergency room with severe epigastric pain, without fevers or significant weight loss. He had immigrated to Canada from the Philippines in 2001. He denied a personal history of TB, however, he did report that his father had received treatment for active TB. An abdominal CT revealed intrahepatic and extrahepatic bile tree dilation with an abrupt transition in the pancreatic head, possible stricture, as well as mucosal thickening of the duodenum at the level of the abrupt narrowing of the dilated common bile duct, concerning for malignancy. Initial laboratory investigations revealed WBC 6.1 x10E9 cells/L, amylase 114 U/L and lipase 59 U/L. Malignancy work up revealed a normal Ca 19-9 at 29.6 kU/L. HIV testing was negative. CT chest revealed bilateral apical fibrotic lesions and smaller lesions throughout the upper and mid-zones bilaterally, suggestive of progressive massive fibrosis. This was in keeping with the patient's former occupation as a miner. There was no evidence of granulomatous disease. EUS was undertaken and this revealed a mass in the head of the pancreas measuring 29 x 29 mm. The mass was invading into the common bile duct. The pancreatic head mass appeared to be invading into the duodenum, as a necrotic ulcerating lesion was also identified in the second part of the duodenum and this was biopsied. The surgical pathology returned as necrotizing granuloma, however, the tissue could not be tested for TB. The patient underwent a repeat endoscopy which again revealed a fungating and friable mass in the second part of the duodenum with biopsies taken. Pathology revealed mild chronic inflammation. Staining for Acid Fast Bacilli was negative, however, Mycobacterium Tuberculosis Complex was isolated on tissue culture. The patient was diagnosed with pancreatic TB and initiated on pyrazinamide, ethambutol, isoniazid and rifampin. Conclusions: Pancreatic involvement by TB is very rare but it has been increasingly reported in both immunocompromised and immunocompetent populations. Symptomatically, pancreatic TB can present with a multitude of non-specific symptoms, including epigastric pain, fever, anorexia, weight loss, or jaundice. In addition, imaging findings of pancreatic TB may mimic malignancy. Our patient, from an endemic area, presented with epigastric pain consistent with the existing literature on pancreatic TB. Isolated pancreatic TB is a rare clinical entity but should be in the list of differential diagnoses in a patient with pancreatic mass especially in the setting of risk factors of TB. Funding Agencies: None